2009
DOI: 10.1124/jpet.109.158113
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Blockade Enhances the Antiproteinuric Effect of an Angiotensin II Blocker through Inhibiting Podocyte Injury in Type 2 Diabetic Rats

Abstract: Treatment with angiotensin II type 1 receptor blockers (ARBs) is the first-line therapy for hypertensive patients with diabetic nephropathy. However, emerging clinical evidence indicates that mineralocorticoid receptor (MR) blockers have blood pressure-independent antiproteinuric effects. We sought to determine whether treatment with an MR blocker, eplerenone, enhances the effects of an ARB, telmisartan, on podocyte injury and proteinuria in type 2 diabetic Otsuka-Long-Evans-Tokushima-Fatty (OLETF) rats. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
1
33
1
3
Order By: Relevance
“…14) Recent studies indicate that glomerular podocyte injury is a cardinal feature of diabetic nephropathy, and is closely involved in the progression of proteinuria, glomerular sclerosis, and tubulointerstitial injury. 14,15) In the present study, we demonstrated that nephrin and podocin protein expression were decreased and desmin staining was increased in DS rats with end-stage HF and that these expressions were restored by the V 2 R antagonist tolvaptan. Nishiyama, et al reported that podocyte injury with decreased nephrin and podocin expression is observed in some experimental models.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…14) Recent studies indicate that glomerular podocyte injury is a cardinal feature of diabetic nephropathy, and is closely involved in the progression of proteinuria, glomerular sclerosis, and tubulointerstitial injury. 14,15) In the present study, we demonstrated that nephrin and podocin protein expression were decreased and desmin staining was increased in DS rats with end-stage HF and that these expressions were restored by the V 2 R antagonist tolvaptan. Nishiyama, et al reported that podocyte injury with decreased nephrin and podocin expression is observed in some experimental models.…”
Section: Discussionmentioning
confidence: 62%
“…Nishiyama, et al reported that podocyte injury with decreased nephrin and podocin expression is observed in some experimental models. 15,16) With regard to the V 2 -mediated action of vasopressin, the use of a highly selective, orally active V 2 R antagonist, SR-121463, in diabetic rats established the critical role played by the antidiuretic effects of vasopressin in urinary albumin excretion associated with diabetes. 17) Recently, Okada, et al 18) showed that tolvaptan is protective against podocyte damage and proteinuria, and that tolvaptan exerts a renoprotective effect by affecting podocyte morphology and function in puromycin aminonucleoside nephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, systemic MR blockade reduces podocyte loss or damage in diabetic rats. 11,12 Therefore, our data showing a lack of prevention of albuminuria in diseased mice with systemic MR blockade or podocyte MR deficiency indicates that podocyte damage in this rapidly progressive GN model is mediated by injury mechanisms that are independent of MR. However, the ability of MR antagonists to reduce proteinuria in CKD, suggests that podocyte MR signaling may play a role in chronic proteinuria.…”
Section: Discussionmentioning
confidence: 97%
“…2,3,5,11 These studies also link MR blockade to suppression of leukocyte recruitment and podocyte injury. This suggests that the major pathologic effects of MR signaling may occur in podocytes and inflammatory cells.…”
mentioning
confidence: 99%
“…Moreover, treatment with tempol or eplerenone markedly attenuated podocyte injury and proteinuria in other rodent models of hypertensive glomerulosclerosis (14,48,50). We also showed that eplerenone attenuated podocyte injury and proteinuria in type 2 diabetic rats (51). Preliminary experiments have shown that aldosterone significantly protracts wound healing in cultured mouse podocytes (52), although the precise molecular mechanisms are not yet clear.…”
Section: Podocyte Injury and Aldosteronementioning
confidence: 79%